Survey of the E-Business Opportunities in Macedonia - Ajanovski, Vangel; Stanoeva-Slabeva, Katarina; Kon-Popovska, Margita; Mishev, Anastas (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2003)
According to many experts’ forecasts, electronic commerce will have increasingly bigger influence on the economic growth on of each country. This is especially true for the smaller countries, like Macedonia, helping them to overcome the regional barriers and to open themselves to the word businesses. In order to identify and analyze the potentials of the Macedonian companies towards using the Internet and New media in their day-to-day business, we have performed a survey among the Macedonian companies. The survey itself has been developed in collaboration with the St. Galen University in Switzerland, in the framework of the project “The Potential of B-B Platforms for the Macedonian industry –Technical and Economic Aspects”. The aim of the survey is to identify the potentials enabled by e-Business, but also to provide us with the necessary information for developing a simple guide on the new technologies that would help the companies to adopt them as seamlessly as possible. The questionnaire was developed in three models: form the companies using Internet, for the ones not using Internet and for the Internet service providers. The accent was stronger on the companies that already using some basic Internet services as they are identified as the early adopters of the e-Business technologies. The survey included questions concerning general company info, computer equipment, basic and advanced Internet usage. Technologies like intranets and extranets, e-commerce, eprocurements, supply chain management and electronic data interchange are also included. Equally important are the data gained from the ISPs, since they provide the foundation for the advanced business usage of the Internet. The results of the survey are processed using standard statistical techniques and some conclusions are made out of them.
Keywords: e-business, b2b